Active listening: The key of successful communication in hospital managers - Jahromi, Vahid Kohpeima (Electron Physician, 2016)
INTRODUCTION: One of the important causes of medical errors and unintentional harm to patients is ineffective communication. The important part of this skill, in case it has been forgotten, is listening. The objective of this study was to determine whether managers in hospitals listen actively. METHODS: This study was conducted between May and June 2014 among three levels of managers at teaching hospitals in Kerman, Iran. Active Listening skill among hospital managers was measured by self-made Active Listening Skill Scale (ALSS), which consists of the key elements of active listening and has five subscales, i.e., Avoiding Interruption, Maintaining Interest, Postponing Evaluation, Organizing Information, and Showing Interest. The data were analyzed by IBM-SPSS software, version 20, and the Pearson product-moment correlation coefficient, the chi-squared test, and multiple linear regressions. RESULTS: The mean score of active listening in hospital managers was 2.32 out of 3.The highest score (2.27) was obtained by the first-level managers, and the top managers got the lowest score (2.16). Hospital mangers were best in showing interest and worst in avoiding interruptions. The area of employment was a significant predictor of avoiding interruption and the managers’ gender was a strong predictor of skill in maintaining interest (p < 0.05). The type of management and education can predict postponing evaluation, and the length of employment can predict showing interest (p < 0.05). CONCLUSION: There is a necessity for the development of strategies to create more awareness among the hospital managers concerning their active listening skills.